1994
DOI: 10.1111/j.1600-0609.1994.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased intracellular concentrations of doxorubicin in resistant lymphoma cells in vivo by concomitant therapy with verapamil and cyclosporin A

Abstract: The tumor cell uptake of doxorubicin was studied in vivo in cells from 2 patients with clinically resistant leukemic lymphomas treated with continous infusions of doxorubicin 9 mg/m2 and vincristine with oral dexamethason. After 24 hours, intravenous or oral verapamil was added and in one treatment course intravenous cyclosporin A was given. Plasma and intracellular doxorubicin concentrations and plasma concentrations of verapamil and norverapamil were determined with HPLC. In the 1st patient the intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This equates to 315 and 20 nM, respectively, which is within the wide range used herein (0.01 nM to 100 μM). Furthermore, the documented intracellular concentration of doxorubicin within tumour cells range from 0.007 to 0.013 nmol/mg protein and 0.027 to 0.086 nmol/mg protein, before and after concomitant therapy with verapamil and cyclosporine (Tidefelt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This equates to 315 and 20 nM, respectively, which is within the wide range used herein (0.01 nM to 100 μM). Furthermore, the documented intracellular concentration of doxorubicin within tumour cells range from 0.007 to 0.013 nmol/mg protein and 0.027 to 0.086 nmol/mg protein, before and after concomitant therapy with verapamil and cyclosporine (Tidefelt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This drug efflux pump can be inhibited by verapamil, too, the research made in vitro proved that it can reduce multidrug resistance. In such a study conducted in two patients with leukemic lymphoma resistant to treatment, verapamil was able to increase the intracellular amount of doxorubicin (Tidefelt et al, 1994). It was found that verapamil was able to overcome the P-gp -mediated resistance to doxorubicin and vincristine in a canine cell line of B cell lymphoma (GL-1) (Uozurmi et al, 2005, as cited in .…”
Section: Abc Transporters and Cholesterol Homeostasismentioning
confidence: 99%